(untitled) (Italian Journal of Public Health, 2011)
Methods: Messages broadcasted by the press were compared with national and international recommendations regarding influenza vaccine. All of the issues of the 5 best selling national newspapers and the 2 best selling general magazines were read from 15 October 2009 to 15 November 2009 in order to select the articles that addressed influenza vaccination. The major messages extracted from these articles were compared with the scientific literature. Results: 217 articles out of 160 newspaper issues and 7 articles out of 8 magazine issues were selected. Articles mainly focused on the vaccine target population and on health care workers reluctance to be vaccinated. Dosage, side effects, efficacy and safety were other recurrent topics. Press-reported messages were largely consistent with the scientific literature, except for the time interval needed between H1N1 and seasonal influenza vaccine administration. Discussion: The issue of vaccination against the H1N1 pandemic influenza received broad media attention during the study period. The information reported was usually correct, but sometimes it failed to convey clear messages. In particular, concern regarding potential side effects and the low uptake of vaccination in healthcare workers appears to have been associated with the very low vaccine uptake in the general population.